Liver Pathology 2021
DOI: 10.5772/intechopen.89177
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Hepatopathy

Abstract: Liver disease resulting from heart disease has generally been referred as "cardiac hepatopathy." The two main forms of cardiac hepatopathy are acute cardiogenic liver injury (ACLI) and congestive hepatopathy (CH). ACLI most commonly occurs in the setting of acute cardiocirculatory failure, whereas CH results from passive venous congestion in the setting of chronic right-sided heart failure (HF). Both conditions often coexist and potentiate the deleterious effects of each other on the liver. In CH, the chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Researchers propose that the mechanism behind this phenomenon is due to the activation of hepatic stellate cells via stimulation of protease-activated receptors. 15,16 Altogether, the impairment of hepatic arterial blood flow in combination with limited oxygen diffusion causes hepatocyte ischemia in HF. 16 Chronic hepatic ischemia causes inflammation and cell death that will eventually lead to fibrosis, and possibly cirrhosis.…”
Section: Congestive Hepatopathymentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers propose that the mechanism behind this phenomenon is due to the activation of hepatic stellate cells via stimulation of protease-activated receptors. 15,16 Altogether, the impairment of hepatic arterial blood flow in combination with limited oxygen diffusion causes hepatocyte ischemia in HF. 16 Chronic hepatic ischemia causes inflammation and cell death that will eventually lead to fibrosis, and possibly cirrhosis.…”
Section: Congestive Hepatopathymentioning
confidence: 99%
“…49,50 While angiotensin-converting enzyme (ACE) inhibitors have a role in the treatment of symptomatic HF, they are contraindicated in patients with decompensated cirrhosis due to the consequences of their vasodilatory effect on systemic hypotension. 15,45 A detailed discussion regarding the management of ascites can be found in Section III A5 (Management of Complications). 50 Cardiac transplantation is another means of therapy for CH and will be discussed in the second part of this review.…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Louie et al 21 reported no significant difference in posttransplant mortality or in liver failure between patients with or without bridging liver fibrosis. 21,22 This has inspired researchers to create an ever increasing number of available noninvasive tests with which to detect fibrosis. These noninvasive tests can be broadly sorted into 2 main categories: serum markers and radiographic imaging.…”
Section: Heart Transplantationmentioning
confidence: 99%